IMPACT OF MATERNAL ANAEMIA ON NEONATAL OUTCOMES: A SINGLE-CENTRE EXPERIENCE - Dostović Hamidović, Lejla; Skokic, Fahrija; Muratovic, Selma; Terzic, Asja (Sanamed, 2025)
Background: Maternal anaemia is one of the most common complications of pregnancy and is associated with adverse outcomes such as preterm delivery, impaired fetal development, and increased risks of morbidity and mortality in the perinatal period. The high prevalence of anaemia in pregnancy and its impact on fetal development represents a significant public health issue. The aim of this study was to analyze the influence of maternal anaemia on neonatal outcomes. Patients and Methods: In a two-year prospective study conducted at the Clinic of Gynecology and Obstetrics and the Clinic of Children’s Diseases of the University Clinical Center Tuzla, 177 newborns and their mothers were analyzed—127 in the experimental group (mothers with anaemia) and 50 in the control group (without anaemia). Sociodemographic and clinical data of the mothers and newborns were collected. Data were processed using conventional statistical techniques. Ethical approval was obtained from the relevant institutional review board. Results: Of the 120 (70.58%) mothers with anaemia included in the study, 106 (88.3%) were between 18 and <35 years of age. Working mothers had lower odds of anaemia (p = 0.025), while mothers who did not use supplements during pregnancy had higher odds (p = 0.001). Maternal anaemia was significantly associated with smoking or tobacco use (p = 0.015). Mothers living outside of marriage were more likely to be anaemic. A higher percentage of vaginal bleeding (p = 0.0001), uncontrolled pregnancies (p = 0.011), and caesarean section as the mode of delivery (p = 0.000) were recorded among anaemic mothers. Babies born to anaemic mothers had lower birth weight compared to those born to non-anaemic mothers (p = 0.004). Maternal anaemia significantly affected gestational age (p = 0.024) and Apgar scores in the 1st (p = 0.006) and 5th minutes (p = 0.0031). In this study, maternal anaemia during pregnancy had a statistically significant impact on perinatal outcomes including perinatal asphyxia, respiratory distress syndrome, neonatal infections, icterus neonatorum, intracranial hemorrhage, and hypoxic-ischemic encephalopathy. Conclusion: In developing countries, current strategies for the prevention of anaemia in pregnancy have had limited success. Programs for careful monitoring and management of anaemia during pregnancy need to be developed in order to prevent poor perinatal outcomes.